A Bibliometric Analysis of Transportation Sector Transformation through Green Policies - Judijanto, Loso; Bunyamin, Ilham Akbar; Arini, Rani Eka (West Science Social and Humanities Studies, 2025)
The transportation sector plays a critical role in economic development and societal mobility but is also a significant contributor to greenhouse gas emissions and environmental degradation. As global efforts to mitigate climate change intensify, green policies have emerged as essential mechanisms for transforming transportation systems toward sustainability. This study conducts a bibliometric analysis using VOSviewer, based on Scopus-indexed publications, to explore the evolution of research on transportation sector transformation through green policies. The findings reveal key thematic trends, including an early emphasis on emissions reduction and climate change, followed by a growing focus on renewable energy integration, electric vehicles, hydrogen fuels, and policy interventions. Co-authorship network analysis highlights fragmentation in global research collaborations, with dominant contributions from China, the United States, and Europe, but limited representation from developing economies. The results suggest that policy frameworks, technological innovations, and economic incentives play a vital role in shaping the transition to sustainable transportation. However, greater interdisciplinary collaboration and research inclusivity are needed to develop globally adaptable strategies. This study provides valuable insights for policymakers, researchers, and industry stakeholders seeking to enhance the sustainability of transportation systems through evidence-based policy and technological innovation.